Magnetohydrodynamics phenomena in continuous casting process under applied electromagnetic braking (EMBr) - Alexander Vakhrushev; Ebrahim Karimi-Sibaki; Menghuai Wu; Mohamad Al Nasser; Gernot Hackl; Yong Tang; Josef Watzinger; Jan Boháček; Abdellah Kharicha (International Journal of Thermofluids, 2025)
In the presented work the effects of electromagnetic braking (EMBr) are gathered, exemplifying key magnetohydrodynamics (MHD) phenomena in continuous casting (CC) process. The complex interactions between turbulent liquid metal flows and a direct current (DC) magnetic field through the meso‑to-macro scale cascade are reviewed. We analyze MHD influences on different types of melt motion in CC, including jets, recirculation zones, and shear flows, as well as Lorentz force-induced acceleration in stagnant regions. These phenomena result from the distribution of induced electric current lines closing through either the liquid bulk or the semiconducting solidifying shell. The continuously growing shell, formed against the water-cooled copper mold walls, is significantly affected by the hot melt flow patterns. The study highlights practical applications of EMBr to optimize flow dynamics in the CC process, providing insight into improving casting stability and product quality.